2018
DOI: 10.11118/actaun201866061549
|View full text |Cite
|
Sign up to set email alerts
|

Regional Branding: Customer's Experience with the Certified Products

Abstract: This article focuses on the experience of Czech customers with the purchase of products labelled by the Association of Regional Brands and Bohemian Paradise Association. The aim of this paper is to evaluate selected indicators associated with purchasing certified regional products. The studied characteristics focus on the knowledge and perception of several chosen microregional brands and on the purchase of a certified product itself. The article presents the results of research conducted through a questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Unlike GP and RA, CP ranked third place in affecting BPRB based on our empirical analysis. Margarisová et al [91] found that for the efficient use of regional products and demand support, it is necessary to define a regional product from a customer perspective. As Xu and Zhao [5] also revealed that the embeddedness of cultural elements within RB products has a positive effect on the consumers' loyalty, which can accordingly promote the performance of RBs.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Unlike GP and RA, CP ranked third place in affecting BPRB based on our empirical analysis. Margarisová et al [91] found that for the efficient use of regional products and demand support, it is necessary to define a regional product from a customer perspective. As Xu and Zhao [5] also revealed that the embeddedness of cultural elements within RB products has a positive effect on the consumers' loyalty, which can accordingly promote the performance of RBs.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Another important criterion was the importance of the individual food labels on the market. The "Klasa" label can be viewed as the main food quality labeling program in the Czech Republic [38][39][40]; the "regional food" label has gradually gained significant importance as well [30], as a result of strong marketing support from the Ministry of Agriculture [41]. The BIO label derives its importance on the Czech market from the increasing interest of the consumers in bio-food production [49].…”
Section: Methodsmentioning
confidence: 99%
“…and can be seen as the main quality program in the Czech Republic [30,[38][39][40]. This label has a strong marketing support from the state authorities, such as the Czech Ministry of Agriculture (MoA) and State Agricultural Intervention Fund; paradoxically, the label is subject to strong criticism from the public for not meeting its goals, i.e., labeling food of superior quality [41]. The label "Czech product-guaranteed by the Federation of the Food and Drink Industries of the Czech Republic" ( Český výrobekgarantováno Potravinářskou komorou ČR) signals that the product was manufactured in Czechia and contains a certain share of Czech ingredients, the production company is owned by a Czech citizen, and the revenue is not transferred outside of the country [4].…”
Section: Introductionmentioning
confidence: 99%
“…But amidst global advancements, it is important to learn from historical evidences and practices which are so immune to our subconscious dialects and create everlasting experiences in how we behave in our every day economic decision making [21]. Such circumstances brings in forced innovation often misinterpreted as disruptive innovation practices during crisis points like Covid-19 which creates best practices strategies [22]. The utility of experiential marketing by using audio and visual aids were prolonged but the recent dimensions of olfactory branding has gained momentum wherein the utility of all the five senses are utilized in brand development and understanding how the brand can be cognitively positioned to create competitive advantages [23].…”
Section: Deduction / обобщениеmentioning
confidence: 99%